Probing the Proton-Coupled Electron-Transfer (PCET) reactivity of a cross-conjugated cruciform chromophore by redox-state-dependent fluorescence - Wagner, Conrad; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2019)
Proton-coupled electron transfer (PCET) reactions are of great importance in synthetic chemistry and in biology, but the acquisition of kinetic information for these reactions is often difficult. Herein, we report the synthesis of a new PCET reagent, showing redox-state dependent fluorescence, by merging the concept of cross-conjugated cruciform chromophores with the strategy of imposing redox activity and Brønsted basicity to aromatic compounds by substitution with guanidino groups. The compound is isolated and characterized in all stable states—reduced, twofold and fourfold protonated and twofold oxidized—and then applied in PCET reactions by using its redox-state dependent fluorescence signal for kinetic measurements.
Gesehen am 19.07.2019